Pengaruh Kualitas Pelayanan dan Penetapan Harga terhadap Kepuasan Konsumen pada Hotel Mona Plaza Pekanbaru - Endang Sutrisna; Haifa Heryani Putri (Departement of Mathematics Education, 2023)
This study aims to determine the effect of service quality and pricing on consumer satisfaction. The method used in this research is descriptive and quantitative statistics, the source of the data in this study came from primary data obtained through the process of distributing questionnaires which were then carried out statistical tests with the SPSS program and secondary data using room sales data at the Mona Plaza Hotel Pekanbaru for the period 2017- 2021. Samples were taken as many as 100 respondents using accidental sampling technique. The data analysis technique used is quantitative analysis using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, partial test, simultaneous test. The test results in this study indicate that partially the service quality variable (X1) has a positive and significant effect on customer satisfaction (Y), partially the pricing variable (X2) has a positive and significant effect on customer satisfaction (Y). And simultaneously service quality (X1) and pricing (X2) have a positive and significant effect on customer satisfaction (Y).